Introduction to the documentation of video games that manage complex narrative variables to introduce political messages - Mouriño, Adrián Suárez (Cuadernos de Documentación Multimedia, 2024)
Through the graduation of the following four variables typical of the study of complex narratives: restrictiveness, depth, self-awareness and communicability, different subjectivities can be generated, different ways of understanding a digital society as a reflection of the real ones and construct immersions in them that affect as players from a political approach. In this text we address this issue, providing a methodology to document video games with a political context that avoid appearing to be so by grading these aforementioned variables in their favor.